Analisis Perbandingan Keputusan Membeli di Pasar Tradisional dan Modern - Titin Agustin Nengsih; Fani Kurniawan; Ahmad Syukron Prasaja (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2021)
The purpose of this study is to determine whether there is an effect of price and service on buying decisions in the traditional market and the modern market in Bayung Lencir. The research method used is quantitative and the population in this study has no known number of respondents, so the sample determination uses the Lameshow formula with an error of 10%. The sample in this study were 100 respondents from traditional markets and 100 respondents from modern markets. The results of hypothesis testing indicate that there is a significant influence between price and purchasing decisions in traditional markets. However, price does not have a significant effect on buying decisions in the modern market. In the modern market, services have a significant effect on purchasing decisions, while services have no significant effect on buying decisions in the Bayung Lencir traditional market. The results of the F-Test indicate that the purchasing decisions of the community are influenced jointly by prices and services in both traditional market and modern market. The R2 value of traditional markets is 52.1%, in other hand R2 value of the modern market is 59.2%.